First record of Holoptilinae from Pakistan, with the redescription of Holoptilus fasciatus (Hemiptera: Reduviidae) - Shah, Syed Ishfaq Ali; Ahmad, Azaz; Li, Hu; Cai, Wanzhi (Zootaxa, 2019)
The assassin bug subfamily Holoptilinae (Hemiptera: Heteroptera: Reduviidae) is recorded from Pakistan for the first time. Holoptilus fasciatus Reuter, 1881, newly recorded from Pakistan, is redescribed, its dorsal habitus and diagnostic morphological characters are illustrated.